Pengaruh Distribusi Dan Kualitas Layanan Terhadap Kepuasan Pelanggan Pada PT. Pos Indonesia Kota Gunungsitoli - Gea, Jeliswan Berkat Iman Jaya; Halawa, Odaligoziduhu; Telaumbanua, Aferiaman (Jurnal Ilmiah Manajemen dan Bisnis (JIMBI), 2025)
This research aims to analyze the influence of distribution quality and service on customer loyalty at PT. Pos Indonesia in Gunungsitoli City. This study is descriptive quantitative in nature, involving a series of processes from data collection, processing, to data interpretation through the application of equations to produce an accurate depiction of the researched conditions based on the obtained data. Based on the analysis using SPSS version 24 software, the results indicate a significant influence of distribution quality and service on customer loyalty at PT. Pos Indonesia in Gunungsitoli City, with a significance value (sig) of 0.000, which is smaller than 0.05, and a contribution of 33%. The findings of this research are expected to encourage sustainable improvements in the distribution system and service quality, thereby realizing customer loyalty and supporting the company's competitiveness against other competitors.